2022
DOI: 10.2196/34745
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Patient Portal Use and Perceived Patient-Centered Communication Among Adults With Cancer: Cross-sectional Survey Study

Abstract: Background Patient-centered communication (PCC) plays a vital role in effective cancer management and care. Patient portals are increasingly available to patients and hold potential as a valuable tool to facilitate PCC. However, whether more frequent use of patient portals is associated with increased perceived PCC and which mechanisms might mediate this relationship have not been fully studied. Objective The goal of this study was to investigate the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 86 publications
(98 reference statements)
1
10
0
Order By: Relevance
“…This may indicate that patient-provider direct communication is important. Private eHealth use focused on the patient portal use in HINTS, and patient portal use is associated with positive PCC in the literature [ 25 ]. On the contrary, public eHealth with no restricted information and no focused communication target, often acted as an adjunct means to obtain needed health information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may indicate that patient-provider direct communication is important. Private eHealth use focused on the patient portal use in HINTS, and patient portal use is associated with positive PCC in the literature [ 25 ]. On the contrary, public eHealth with no restricted information and no focused communication target, often acted as an adjunct means to obtain needed health information.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in past studies. Individuals’ PCC has been positively associated with personal health record use (e.g., patient portal) [ 25 , 33 ]. Patients who used a patient portal more frequently tended to have better self-management behavior especially among ones with multimorbidity [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIT is not able to incorporate emotional experiences, even though it may change with wider adoption of artificial intelligence in the health care universe [ 61 ]. Instead, it is a facilitator of engagement behaviors that could potentially bridge socioeconomic and communication gaps [ 36 , 62 , 63 ]. Even when patients mostly rely on medical professionals for medical knowledge regarding their diagnosis and treatment [ 64 ], those with better access to medical information technology support have a more positive attitude toward engaging in medical decision-making, as it helps in relative information seeking to relieve anxiety [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although further research is needed on the use of HIT among older adults diagnosed with cancer, it has been observed that these patients tend to demonstrate higher levels of activation and engagement in their health care. This can be attributed to the existing body of literature that underscores the advantages of HIT and the supportive role played by oncology health care providers [ 32 - 36 ]. Therefore, to investigate the influence of HIT use in older adults, we examined specific sociodemographic and psychosocial factors of fatalistic beliefs while accounting for the potential impact of a cancer diagnosis, which might affect their level of engagement.…”
Section: Introductionmentioning
confidence: 99%